Spatial visual music - the combination of visual music and physical space - Yang, Jing (Nanyang Technological University, 2020)
The current study serves as an experiment of an artistic approach in which Visual Music is combined with the utilization of physical space to enhance emotional expression and evocation. Instead of treating the space as mere a container of artworks, the current study considers the parameters of space as compositional elements, which can be composed musically according to the artistic emotion that needs to be conveyed. In the current thesis, the author proposes a concept called “Spatial Visual Music” as a sub-genre of Visual Music. With the emphasis on the qualifier “spatial”, this term refers to a particular type of Visual Music creation in which the artists compose not only the sounds and visuals, but also the space (spatial parameters). The term “Spatial Visual Music” is thus defined as a type of artistic expression, which requires the act of using spatial parameters as compositional elements to compose music-like spatial relationships, and construct a space as a three-dimensional visual score. A term called “entitative space”, which roots in the Chinese classical art aesthetics and Taoist ideology, is also proposed in the current thesis. With the incorporation of the concept of “entitative space”, spatial parameters are imported into Visual Music composition as compositional elements in addition to visual and auditory parameters. The enrichment of compositional materials has the potential of extending the flexibility of Visual Music creation process, providing additional information, influencing the audience’s emotional response, and enriching interactive activities for Visual Music artworks. The main contents of this thesis consists of three parts: The first part is literature review, from Chapter 2 to Chapter 3, which involves the historic trace of Visual Music studies, the basic theory of physical space and the concept of perceptual space, and a review of the utilization of space in different art forms. The second part is the theoretical proposition, where the author proposes a new term called “Spatial Visual Music”, a structure of Spatial Visual Music, and two concepts called “Memoryscape” and “Digital-Cortex” which provide the theoretical foundation for artistic practice. The third part introduces the experimental artistic practices designed under the instruction of the proposed theoretical framework of Spatial Visual Music.